131I radioactive self-expandable metallic stents for the therapy of malignant biliary obstruction. Issue 1 (April 2021) - Liu, Meirong; Hou, Mengfei; Wu, Qinghe; Zhang, Chunfu
Abstract: Biliary stent implantation has become a standard approach for patients with unresectable malignant biliary obstruction. Unfortunately, in-stent restenosis after stent implantation still occurs because of tumor overgrowth. The majority of studies show that radioactive stents harbor both the obstructed biliary tract-dilating and tumor-suppressing functions. In this study, we designed a kind of novel 131 I-labeled radioactive self-expandable metallic stent (SEMS) that combines the mechanical dilation forces induced by stent expansion and 131 I intraluminal brachytherapy, which was prepared by first coating the SEMS with poly (diallyl acrylate) (PDA) and then labeling with iodine-131. The designed stents would not only have a longer patency time but also is able to inhibit biliary compression caused by tumor growth. The PDA coating was robust and flexible. The 131 I labeling rate was about 60%, and after a 16-day test of radiochemical stability of 131 I, the radioactive stability was around 80%. In addition, the radiochemical stability of 131 I could be improved by PDA recoating post- 131 I labeling. In conclusion, we designed and fabricated a kind of novel 131 I-labeled radioactive self-expandable metal stents by labeling 131 I on the PDA-coated stent. We provide a new idea of radioactive stents design, which would extend the patency time of the stent while reducing the rate of stent restenosis after implantation.